PENGARUH RELATIONSHIP MARKETING, KUALITAS PRODUK INTERNET BANKING DAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH PADA BANK BRI UNIT MEDAN SUNGGAL - TINA MUHARDIKA HANDAYANI (JURNAL ILMIAH MAKSITEK, 2020)
This study aims to determine the effect of Relationship Marketing, Internet Banking Product Quality and CustomerSatisfaction on Customer Loyalty at BRI Bank Medan Sunggal Unit, with a population of 100 people with samplingtechniques using slovin. Data collection techniques used are through questionnaires, namely by spread questionnaire. Theprerequisite test analysis includes normality test, multicollinearity test, and heteroscedasticity test. Data analysis techniquesare using t test, f test, multiple linear regression and determinant coefficient test. The results showed that (1) there was apositive and significant relationship between Relationship Marketing and Customer Loyalty at the BRI Bank Medan SunggalUnit, with tcount 2.131> t table 1.66088 and the significance value was lower than 0.05, 0.036, (2) there was a positiveinfluence and significant Internet Banking Product Quality on Customer Loyalty at BRI Bank Medan Sunggal Unit, with tcount4.132> t table 1.66088 and its significance value is less than 0.05 i.e. 0,000 (3) there is a positive and significant influence onCustomer Satisfaction on Customer Loyalty at the Bank BRI Unit Medan Sunggal, with t count 2.706> t table 1.66088 and itssignificance value is less than 0.05 i.e. 0.008 (4) there is a positive and significant influence on Relationship Marketing,Internet Banking Product Quality and Customer Satisfaction on Customer Loyalty at Bank BRI Unit Medan Sunggal withFcount 37.096> F table 2.31 and the significance value is smaller than 0.05 yait u 0,000.